Free-Will in The Block Universe? Old and New Problems with Time Travels - Soler Gil, Francisco José; Alfonseca, Manuel (Philosophia, 2019)
This paper discusses Carl Hoefer‘s thesis in his article "Freedom from the inside out": to make the block universe compatible withÂ free-will, one must avoid presentist intuitions intuitively associated to free actions. We show a possible difficulty of this proposal: the assumption of the block universe can imply that certain free actions would be cross-linked in a way incompatible with freedom. This is shown in a graphical way often used in the discussion of freedom in the block universe, by means of a thought experiment with time machines. This difficulty does not depend on the real existence of those machines.